ANALISIS KOHESI GRAMATIKAL TEKS PIDATO PRABOWO DALAM PEMILIHAN CALON PRESIDEN DAN CALON WAKIL PRESIDEN TAHUN 2019 - Sultan Sultan (STKIP PGRI Jombang, 2019)
Research on Grammatical Cohesion Analysis of Prabowo's Speech Text in the Election of Presidential Candidates and Vice-Presidential Candidates in 2019 discusses the forms of references and substitutions using the Mulyana Discourse Study theory. The aim is to describe the form of references and substitutions that are used as references to words or sentences directed by an author to indicate the direction or reference or purpose intended by the writer, so that the meaning that is to be conveyed is clearer.The method used in this research is descriptive qualitative. The reason researchers used descriptive qualitative research methods in this study, because researchers describe words that include forms of reference and substitution in Prabowo's Speech Text in the Election of Presidential Candidates and Vice Presidential Candidates in 2019. Data collection is done by observation, object determination, data reading, data identification, coding, and data classification.The results of this study indicate that there are words that are included in the form of endophoric references, exophoric references, and forms of substitution. The most common data found is the grammatical aspect of exophoric reference. It can be concluded that the words used in Prabowo's speech text are many words that are repeated, so that the use in the form of references and substitutions in Prabowo's Speech Text in the Election of Presidential Candidates and Vice Presidential Candidates in 2019 is lacking in cohesion. Thus the thesis has a beneficial hope for the reader by learning more about discourse, especially grammatical cohesion, and might be better developed.